Apropriação tecnológica de docentes da educação profissional na modalidade a distância - Oliveira, Cristiane Tavares Casimiro de (2012)
The present research is part of the Programa de Pós-Graduação em Educação: Currículo PUCSP, alligned with the area of research Novas Tecnologias na Educação. The study was conducted within the context of the course in Technical Marketing, offered in the distance learning (DL) mode by the Instituto Federal de Educação Ciência e Tecnologia do Tocantins (IFTO) and derived from the following problem: what is the relationship between the internship on technological appropriation of teachers and pedagogical use of TDIC during the course? The field research was conducted with former teachers, distance tutors, mentors and managers involved in the course. Accordingly, the qualitative and quantitative approach was selected, using direct observation, application of two questionnaires with closed and open questions, semi-structured interviews, records in the logbook, photographic records, and focus group data collected in the AVA. Based on data analyzed within the theoretical framework the following aspects were observed: the teachers under survey are in the second stage of technological appropriation, according to a study Information Commmunication Technology in Educacion: a curriculum for schools and programe of teacher development published by UNESCO (2002) known as Application of TDIC in the area of specialization. However, considering the study by Sandholtz et.al. (1997), we can infer that teachers are in transition between stages of Adaptation and Appropriation. There are indications that the group has an understanding of the pedagogical use of TDIC which is close to a more advanced phase of technological appropriation than those shown by the analysis of AVA records. According to AVA, the use of TDIC did not meet the expectations of a collaborative and interactive work, as shown by the studies of Almeida (2000, 2003, 2005, 2011). Nevertheless, it presented a character content inconsistent with the characteristics of a work based on a constructionist approach. Although the course is based on the constructionist approach, the lack of teacher training for pedagogical work with TDIC was an important factor, hampering the development of activities based on this approach. We concluded that aspects extrinsic to individuals but that permeate the pedagogical work with the TDIC as well as advancement of the stage of technological appropriation of teacher may often overlap and determine the intrinsic ones, insofar as the structural aspects ( therefore non-pedagogical ones ), determine evasion, rotation and the very existence of a faculty. Thus, while reflecting upon the teacher´s appropriation of the technology and pedagogical use of TDIC one must study the context, the questions posed by the environment in which not only appropriation but also the teacher´s action takes place